2009
DOI: 10.1001/archsurg.2009.2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategy for Intraductal Papillary Mucinous Neoplasm of the Pancreas Based on Malignant Predictive Factors

Abstract: Measurement of the CEA level in pancreatic juice should be considered in the diagnosis of IPMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 20 publications
(30 reference statements)
1
38
0
Order By: Relevance
“…Of these studies, 33 investigated mural nodules5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 21 examined dilatation of the main pancreatic duct (MPD)7 9, 15 16, 18 21, 23 26, 27 30, 32 36, 38, 39, 40, 41, 42, 43, 44, 45, 46, 21 analysed cyst size5 7, 8, 9 14, 15 18, 20 23, 25 27, 28 31, 36 38, 40 41, 43 47, 48, 49, 17 assessed CA19‐9 increase14 …”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, 33 investigated mural nodules5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 21 examined dilatation of the main pancreatic duct (MPD)7 9, 15 16, 18 21, 23 26, 27 30, 32 36, 38, 39, 40, 41, 42, 43, 44, 45, 46, 21 analysed cyst size5 7, 8, 9 14, 15 18, 20 23, 25 27, 28 31, 36 38, 40 41, 43 47, 48, 49, 17 assessed CA19‐9 increase14 …”
Section: Resultsmentioning
confidence: 99%
“…However, the nodule's size has to be considered, because larger nodules are likely to be malignant and smaller ones are likely to be benign [20,21]. Recent studies showed that branch duct IPMNs with mural nodules of more than 5 mm included not a few benign neoplasms [17][18][19]. Therefore, in the present study, branch duct IPMNs without mural nodules or with mural nodules of less than 9 mm were followed up until nodules developed or became enlarged and reached 10 mm, when surgical resection was recommended to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies showed that resection of branch duct IPMNs that had a cyst of more than 30 mm resulted in oversurgery in many cases [6][7][8][9][10]. Although a mural nodule is a predictor of malignancy in branch duct IPMN [6,7,[11][12][13][14][15][16], nodule size has hardly been taken into consideration, with the exception of a few studies which found that branch duct IPMNs with mural nodules of more than 5 mm included not a few benign neoplasms [17][18][19]. In the present study, we followed up branch duct IPMNs without mural nodules and those with mural nodules of less than 9 mm until nodules developed or enlarged to a size of 10 mm, and we investigated whether the size of 10 mm was appropriate as an indicator of surgery for branch duct IPMN.…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant advances in the diagnostic imaging technique, histopathological diagnosis of benign/malignant IPMNs is still difficult (10,23). Histological markers of the malignancy have been not enough, although several indicators for malignant potentials have been reported previously (8,14,21,22,27). It is necessary to understand the molecular features of invasion and metastasis of IPMNs in order to identify an effective therapeutic management for this histologically diverse tumor.…”
mentioning
confidence: 99%